Report of the Managing Director to the International Monetary and Financial Committee on the IMF's Policy Agenda. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
Over the past six months, work has concentrated on making surveillance more effective, reforming quotas and voice, and reviewing the finances of the institution to place them on a sustainable footing. Progress has also been made with other key elements of the medium-term strategy, including capacity building, crisis prevention, and support for emerging markets and low-income countries. In January, the Fund welcomed its 185th member, the Republic of Montenegro.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet